Balancing the risks and benefits is essential for reaping the success of adding in-circuit bacterial filters. Issue 5 (19th May 2022) - Stieglitz, Sven; Mandal, Mohanchandra; Bhakta, Pradipta; Esquinas, Antonio M.
We read the innovative study by Rabec et al . [1] with great interest, in which they evaluated the impact of use of different inline bacterial filters on the performance of non-invasive ventilator (NIV) using positive inspiratory pressure (PIP) ventilation. After analysing the study, we want to raise some points which are vital in interpreting the outcomes of this study. Balancing the benefits and drawbacks is essential to extract the advantages of adding an inline bacterial filter during non-invasive ventilation https://bit.ly/3JDHjwL